Conselho administrativo e os sistemas de gestão e controle estratégico: um estudo de caso em uma empresa de saúde - Boemo, Elisandra de David (2010)
This paper presents a case study in a health care company, located in Santa Maria, RS, Brazil. The objective was to describe and evaluate the implementation of the administrative council and its systems of management and strategic control in a health care company. To achieve this goal was necessary, first, to study how the company was before the deployment of the administrative council, and the changes that occurred after their deployment. Subsequently, was studied the system of strategic management, considering the visioning and strategic planning as well as the system of strategic control, which covered the cost control and budget control. To collect the data was used documents and questionnaires administered to the partners and company managers. We have identified some advantages with the implementation of the administrative council and systems of management and strategic control, including: integration between the partners; communication improvement; more support for the decision-making; and, information transparency.